A study to compare ramosetron and ondansetron for prevention of post-operative nausea and vomiting in patients undergoing laparoscopic cholecystectomy under general anesthesia - Amit Dahiya; Rashmi; Vasudha Govil; Suraj Garg; Ruchika Singhmar; Radhika Malik (Asian Journal of Medical Sciences, 2023)
Background: The incidence of nausea and vomiting following laparoscopic cholecystectomy is very high. 5-hydroxytryptamine receptor antagonists are drug of choice for prevention of post-operative nausea and vomiting (PONV) because of their good efficacy and very few side effects in comparison to other antiemetics. Aims and Objectives: This study was undertaken to compare the efficacy and safety of intravenous ramosetron 0.3 mg and ondansetron 8 mg for prevention of PONV in patients undergoing laparoscopic cholecystectomy under general anesthesia. Materials and Methods: One hundred patients between 18 and 70 years of age with American Society of Anesthesiology Grade I and II scheduled for elective laparoscopic cholecystectomy were randomly divided into two groups of 50 patients each. Group A patients were given injection ondansetron 8 mg and Group B patients were given injection ramosetron 0.3 mg approximately 5 min just before the induction of general anesthesia. Results: Difference in Nausea, vomiting/retching, and PONV score assessed at 4, 8, 12, and 24 h interval postoperatively in both groups was found to be statistically insignificant (P>0.05). The severity of nausea was assessed by visual analogue scale at various time intervals and use of rescue antiemetics in both the groups were found statistically insignificant. Incidence of side effects was also comparable in both the groups. Conclusion: Ramosetron and ondansetron are equally effective for prevention of PONV in patients who underwent elective laparoscopic cholecystectomy under general anesthesia when used prophylactically. Both drugs are safe and have low incidence of side effects.